Production and quality assurance of a Scintillating Fibre detector for the LHCb experiment - Nieswand, S. (Journal of instrumentation, 2017)
To deal with the instantaneous luminosity of the LHC after the Long Shutdown 2 in 2018/19, several subsystems of the LHCb detector have to be exchanged or upgraded. For this purpose, the Scintillating Fibre (SciFi) Tracker is being built to replace the current downstream tracking system. The base of this new tracker are 2.5m long scintillating fibres (O 250[mu]m) in which light is generated by passing charged particles. The fibres are arranged in six-layer fibre mats which are read out with the help of silicon photomultipliers (SiPMs) at the edge of the tracker's acceptance. The tracker will cover an area larger than 340m super(2). To produce the required total of 1024 fibre mats, serial production was set up at several production sites. To assure the quality of the fibre mats, they are subject to various tests during the production. The different production steps as well as the quality assurance measurements will be presented.